Assessing disparities in medical students’ knowledge and attitude about monkeypox: a cross-sectional study of 27 countries across three continents - Abd ElHafeez, Samar; Gebreal, Assem; Khalil, Mohammad Adnan; Youssef, Naglaa; Sallam, Malik; Elshabrawy, Abdelhamid; Abdel-Rahman, Suzan; Mahboob, Amira Saad; Yazbek, Saja; Elbanna, Eman H.; Adhyaru, Riddhi; Rodoshi, Zarin Nudar; et al. (Frontiers in Public Health, 2023)
Background and aims The recent monkeypox (Mpox) outbreak confirmed by the World Health Organization (WHO) underscores the importance of evaluating the knowledge and attitude of medical students toward emerging diseases, given their potential roles as healthcare professionals and sources of public information during outbreaks. This study aimed to assess medical students’ knowledge and attitude about Mpox and to identify factors affecting their level of knowledge and attitude in low-income and high-income countries. Methods A cross-sectional study was conducted on 11,919 medical students from 27 countries. A newly-developed validated questionnaire was used to collect data on knowledge (14 items), attitude (12 items), and baseline criteria. The relationship between a range of factors with knowledge and attitude was studied using univariate and multivariate analyses. Results 46% of the study participants were males; 10.7% were in their sixth year; 54.6% knew about smallpox; 84% received the coronavirus disease 2019 (COVID-19) vaccine; and 12.5% had training on Mpox. 55.3% had good knowledge of Mpox and 51.7% had a positive attitude towards it. Medical students in their third, fifth, or sixth year high- income countries who obtained information on Mpox from friends, research articles, social media and scientific websites were positive predictors for good knowledge. Conversely, being male or coming from high-income countries showed a negative relation with good knowledge about Mpox. Additionally, a positive attitude was directly influenced by residing in urban areas, being in the fifth year of medical education, having knowledge about smallpox and a history of receiving the coronavirus disease 2019 (COVID-19) vaccine. Receiving information about Mpox from social media or scientific websites and possessing good knowledge about Mpox were also predictors of a positive attitude. On the other hand, being male, employed, or receiving a training program about Mpox were inversely predicting positive attitude about Mpox. Conclusion There were differences in knowledge and attitude towards Mpox between medical students in low and high-income countries, emphasizing the need for incorporating epidemiology of re-emerging diseases like Mpox into the medical curriculum to improve disease prevention and control.